A comparison of measured and calculated values of air kerma rates from 137Cs in soil - V. P. Ramzaev; V. Yu. Golikov (Радиационная гигиена)
In 2010, a study was conducted to determine the air gamma dose rate from 137Cs deposited in soil. The gamma dose rate measurements and soil sampling were performed at 30 reference plots from the south-west districts of the Bryansk region (Russia) that had been heavily contaminated as a result of the Chernobyl accident. The 137Cs inventory in the top 20 cm of soil ranged from 260 kBq m–2 to 2800 kBq m–2. Vertical distributions of 137Cs in soil cores (6 samples per a plot) were determined after their sectioning into ten horizontal layers of 2 cm thickness. The vertical distributions of 137Cs in soil were employed to calculate air kerma rates, K, using two independent methods proposed by Saito and Jacob [Radiat. Prot. Dosimetry, 1995, Vol. 58, P. 29–45] and Golikov et al. [Contaminated Forests– Recent Developments in Risk Identification and Future Perspective. Kluwer Academic Publishers, 1999. – P. 333–341]. A very good coincidence between the methods was observed (Spearman’s rank coefficient of correlation = 0.952; P<0.01); on average, a difference between the kerma rates calculated with two methods did not exceed 3%. The calculated air kerma rates agreed with the measured dose rates in air very well (Spearman’s coefficient of correlation = 0.952; P<0.01). For large grassland plots (n=19), the measured dose rates were on average 6% less than the calculated kerma rates. The tested methods for calculating the air dose rate from 137Cs in soil can be recommended for practical studies in radiology and radioecology.